Treatment of high-grade spondylolisthesis with Schanz recoil screws: our experience - Lombardi, Francesco (Springer Berlin Heidelberg, 2013)
PURPOSE: Spondylolisthesis surgical treatment is often difficult with higher degree of slip and related techniques still debated. We have taken into consideration double thread recoil Schanz screws. This system should allow the best reduction of the slip, treating only the affected vertebrae. METHODS: We retrospectively analyzed 46 patients affected by grade II or higher spondylolisthesis, treated with circumferential arthrodesis using Schanz screws. Duration of surgery, complications, reduction, and rate of fusion have been recorded. RESULTS: We found that duration of surgery and complications were similar or slightly lower if compared to our standard Posterior Lumbar Interbody Fusion procedures. However, radiological results and clinical outcome appear better in cases treated with Schanz screws. CONCLUSIONS: Fixation system with Schanz screws seems to be effective in reducing the slip, treating only the affected level, in high grade of spondylolisthesis.